2005
DOI: 10.1063/1.1921147
|View full text |Cite
|
Sign up to set email alerts
|

Solution of the general dynamic equation along approximate fluid trajectories generated by the method of moments

Abstract: We consider condensing flow with droplets that nucleate and grow, but do not slip with respect to the surrounding gas phase. To compute the local droplet size distribution, one could solve the general dynamic equation and the fluid dynamics equations simultaneously. To reduce the overall computational effort of this procedure by roughly an order of magnitude, we propose an alternative procedure, in which the general dynamic equation is initially replaced by moment equations complemented with a closure assumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…͑22͒ is commonly used. In those cases the problem at r ‫ء‬ does not occur due to a time-dependent critical radius, 9 for example. If the critical radius is constant, the GDE therefore cannot be used with the above delta function.…”
Section: General Dynamic Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…͑22͒ is commonly used. In those cases the problem at r ‫ء‬ does not occur due to a time-dependent critical radius, 9 for example. If the critical radius is constant, the GDE therefore cannot be used with the above delta function.…”
Section: General Dynamic Equationmentioning
confidence: 99%
“…Hagmeijer et al 9 applied the GDE to a condensing flow through a nozzle. In this study, the GDE was also used for droplets smaller than critical, while new droplets were still inserted at the critical size.…”
Section: Introductionmentioning
confidence: 99%
“…The algorithm is an extension of the Phase Path Analysis (PPA) algorithm derived for unary systems [20]. It is shown that the resulting cluster size distribution, which has a Dirac δ-function character, agrees well in integral sense with the solution of the NBD equations.…”
Section: Introductionmentioning
confidence: 72%
“…Applications can be found in the fields of condensing vapors [20], cavitation [54], crystallization [18,61], ferromagnetics [57], aerosol and atmospheric science [17], combustion science [41] and chemical processes [26]. In this thesis we will focus on the vapor to liquid phase transition.…”
Section: Condensation Phenomenonmentioning
confidence: 99%
See 1 more Smart Citation